Surgical Treatment of Scoliosis in Marfan Syndrome: A Case Report - Taboridze, Iamze; Aladashvili, Lali; Vardzukashvili, Irakli (European Scientific Journal, ESJ, 2017)
Marfan syndrome (MFS) is a connective tissue disorder of variable inheritance that affects multiple organ systems. Scoliosis affects around 60% of Marfan patients and may progress rapidly during growth spurts, leading to marked deformity, pain and restricted ventilatory deficit. The purpose of this paper is to describe a 13-year-old female patient with Marfan syndrome and surgical treatment of scoliosis. The results indicate that posterior-only surgery with instrumented fixation and fusion is effective and safe for the treatment of scoliosis in selected patients with Marfan syndrome.